Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae) - Hu, Hong-Ying; Triapitsyn, Serguei V. (Zootaxa, 2016)
A new Palaearctic species of Anagrus Haliday (Hymenoptera: Mymaridae), A. turpanicus Triapitsyn & Hu sp. n., is described and illustrated from Xinjiang Uyghur Autonomous Region of China. It was reared from parasitized eggs of the leafhopper Arboridia kakogowana (Matsumura) (Hemiptera: Cicadellidae) (Fig. 10) on cultivated table grapes from Turpan, which had been previously misidentified there as Erythroneura apicalis (Nawa) (e.g., Wang et al. 2004, 2011; Luan et al. 2006). This leafhopper has been an important economic pest in Turpan area since 1998, causing serious damage to the cultivated grapevines (Wang et al. 2004; Luan et al. 2006). Wang et al. (2011) reported that the mite Leptus sp. (Erythraeidae) and several unidentified spider species were the main natural enemies of Erythroneura apicalis in and around Turpan. This is the first record of A. kakogowana from China; it was not included in the key to the Chinese species of the genus Arboridia Zachvatkin by Song & Li (2015). Arboridia kakogowana is native to the eastern Palaearctic region (Japan, Korea, and Far East of Russia), and has been recently recorded as an invasive pest of cultivated grapes in southern Russia (Gnezdilov et al. 2008).